2019
DOI: 10.1177/1042258719867564
|View full text |Cite
|
Sign up to set email alerts
|

The Liability of Volatility and How it Changes Over Time Among New Ventures

Abstract: This article theorizes how short-term revenue volatility affects new venture viability and how such volatility develops over time. Tracking the bank accounts of 6,578 new ventures over a 10-year period, we find that, even after controlling for a range of other factors, short-term revenue volatility is a strong predictor of venture exit. Although short-term revenue volatility is associated with the depletion of buffer resources and financial default, surviving ventures do not, on average, decrease their short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…The Scott hypothesis: venture performance is associated with more volatile growth paths However, there are also drawbacks to erratic growth. Lundmark et al (2020) provide four reasons why volatility is detrimental to firm survival in the context of within-the-year revenue volatility.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The Scott hypothesis: venture performance is associated with more volatile growth paths However, there are also drawbacks to erratic growth. Lundmark et al (2020) provide four reasons why volatility is detrimental to firm survival in the context of within-the-year revenue volatility.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…5 Our indicator of total sales has been used in previous research (e.g. Coad et al 2013;Lundmark et al 2020).…”
Section: Measuring Total Salesmentioning
confidence: 99%
“…4 Note that it is not possible to verify the origins of possible payments by the entrepreneur into the business account in the form of cash or cheque deposits. However, we consider that there is very limited scope for non-sales income to distort significantly the measures that we have selected in a sample of more than 6000 firms.5 The adjustment for inflation is undertaken using World Bank data for the consumer price index for the United Kingdom (GBR), as inLundmark et al (2020): see https://data.worldbank.org/indicator/FP.CPI.TOTL?locations=GB (last accessed 23rd June 2019).…”
mentioning
confidence: 99%
“…Furthermore, survival challenges may be particularly acute for younger firms. The exit hazard is relatively high in the years immediately after entry, but afterwards stabilizes at a lower value, perhaps due to the liability of newness that affects young firms (Lundmark et al, 2019). Indeed, previous work has suggested that firms undergo significant changes in their first 5-7 years after entry (Anyadike- Danes and Hart, 2018;Coad, 2018).…”
Section: Disaggregating By Yearmentioning
confidence: 99%